Pore formation by dimeric Bak and Bax: an unusual pore? - Uren, Rachel T. (Philos Trans R Soc Lond B Biol Sci, 2017)
Apoptotic cell death via the mitochondrial pathway occurs in all vertebrate cells and requires the formation of pores in the mitochondrial outer membrane. Two Bcl-2 protein family members, Bak and Bax, form these pores during apoptosis, and how they do so has been investigated for the last two decades. Many of the conformation changes that occur during their transition to pore-forming proteins have now been delineated. Notably, biochemical, biophysical and structural studies indicate that symmetric homodimers are the basic unit of pore formation. Each dimer contains an extended hydrophobic surface that lies on the outer membrane, and is anchored at either end by a transmembrane domain. Membrane-remodelling events such as positive membrane curvature have been reported to accompany apoptotic pore formation, suggesting Bak and Bax form lipidic pores rather than proteinaceous pores. However, it remains unclear how symmetric dimers assemble to porate the membrane. Here, we review how clusters of dimers and their lipid-mediated interactions provide a molecular explanation for the heterogeneous assemblies of Bak and Bax observed during apoptosis. This article is part of the themed issue ‘Membrane pores: from structure and assembly, to medicine and technology’.